Cyber mobs, trolls, and online harassment - Mikoley, Kate (Topics today, 2022)
"As young people continue to share more of their lives online, social media opens up increasing opportunities for international dialogue, but it also means they run the risk of encountering the problematic parts of a virtual community, such as cyber mobs, bullies, and trolls. This thoroughly researched text takes a deep dive into these issues, examining the reasons they happen, common ways to identify them, and tips for protecting oneself from becoming a victim. Readers use full-color photographs, quotes from experts, sidebars, and discussion questions to develop a comprehensive overview of online issues and take precautions in their digital life"--